BACTERIAL GENE EXPRESSION OF SHEEP POX VIRUS ENCODING ANTIGENIC PROTEINS OF SPPV095 AND SPPV141 FOR THE DEVELOPMENT OF NEW GENERATION SPECIFIC PROPHYLAXIS - Taylakova , E.T.; Chervyakova, O.V. (Eurasian Journal of Applied Biotechnology, 2016)
Vaccination is an effective means of preventing the dissemination of infectious diseases and therefore, improvement of existing prophylactic measured is urgent. Recombinant proteins with antigenic and immunogenic properties have been widely used in recently developed prophylactic preparations. The objective of this study was to generate recombinant proteins of the sheep pox virus for the development of a subunit SPV vaccine, since outbreaks of the infection have been more frequently reported in the republic and threaten the progress of animal husbandry. In this study, the conditions for the expression of the SPV genes sppv-95 and sppv-141 in a bacterial system were optimised. It was shown that recombinant protein expression levels were optimal after incubation at 37°С for 4 h, following induction with 0.5 mM isopropyl-β-D-thiogalactopyranoside (IPTG) for gene sppv-95, and at 25°С and 0.25 mM IGPT for gene sppv-141. The expression of the target recombinant proteins was confirmed by immunoblotting using serum against polyhistidine. The recombinant proteins were shown to interact in serological tests with antibodies to SPV, thus confirming the retention of their specific antigenic activity following expression in a prokaryotic system. The resulting recombinant proteins will be used in the development of prophylactic preparations.